Exploring the ethical decision-making practice among Malaysian consultant quantity surveyors: a qualitative study. (14th December 2022) - Hashim, Nor Atikah; Ismail, Ismi Arif; Idris, Khairuddin; Ahrari, Seyedali; Omar, Zoharah; Zaremohzzabieh, Zeinab
The Malaysian Government has worked tirelessly to develop a comprehensive set of tactics aimed at fighting corruption. One of the sectors that have problems with corruption is the construction industry especially among consultant quantity surveyors (CQS) due to the nature of their work. Many unethical behaviours are being practiced in the construction industry. The goal of this research is to explore the ethical decision-making practice among CQS in Malaysia. Researchers described the results of a qualitative research study involving CQS. Purposive sampling was used to choose interviews. The eight selected respondents were from three main quantity surveyors' institutions. This study employed semi-structured interviews for data gathering. Following the data analysis, seven key themes emerged: 'upbringing', 'skill and training', 'experience and intuitions', 'social interaction', 'adherence to the duty of care', 'company policy' and 'compliance with the ethics code'. Identifying these elements behind ethical decision-making will help the consultant's quantity surveyors to perform their duty well.